Performance improvement of the GAGAN satellite-based augmentation system based on local ionospheric delay estimation in Thailand - Sophan, Somkit; Myint, Lin M.M.; Saito, Susumu; Supnithi, Pornchai (My University, 2022)
Satellite-Based Augmentation System (SBAS) is essential to support aircraft navigation. L1 SBAS operates on the L1 frequency (1575.42 MHz) and is currently still of interest since all GNSS satellites and receivers do not fully support additional frequencies such as L5 (1176.45 MHz). Although the Global Positioning System (GPS) aided Geo Augmented Navigation (GAGAN) SBAS is available, the performances are degraded due to the discrepancies of the ionospheric correction over Thailand and surrounding areas. Hence, in this work, we propose a new method based on the geometry-free ionospheric delay estimation with a single frequency (L1) and a single reference station requirement. The local ionospheric delays are estimated based on the proposed method with the observed GPS and GAGAN data in Thailand. Then the ionospheric corrections are obtained from the estimated local ionospheric delays. The analysis shows that using the estimated corrections, the positioning errors are reduced both on quiet days and locally disturbed days in 2019. More reductions in the positioning errors are found in September and December than other months. In addition, we perform a preliminary availability assessment of two critical phases of flights. The GAGAN performances with the proposed method for the APV-I and LPV-200 categories are improved up to 57% and 53%, respectively, in comparison with the baseline method of the IGP correction.
Keywords: GAGAN; Geometry-free ionospheric delay estimation; GPS; SBAS; Single point positioning